INFLUENCE OF WAVE TYPE ON VIBRATION EFFECT IN LOW PERMEABILITY CORE SAMPLES - Sitompul, Victor
Barabanov in his research showed that S-wave attenuation lower than P-wave so that S-wave as a source of vibration would give better effect than P-wave to increase oil recovery factor. This research showed that P-wave in low permeability would give better effect to increase oli recovery than S-wave. Previous result showed the increase of oil RF, porosity, permeability, and decreasing of Sor using S-wave type (circular mode). Recently, the equipment has developed not only circular mode (S-wave type) as a previous result but also axial mode (P-wave type). This experiment used synthetic core with low (<50 md) to fair permeability on 15 Hz frequency with 0.1 ?m amplitude for P-wave and 0.2 ?m for S-wave. The RF increment reached 8.3% on low permeability (34.8 md) and 10.29% on fair permeability (115.4 md) at same amplitude for P-wave. On vibration stimulation using circular mode, the increment of oil RF only occur on fair permeability.